2022
DOI: 10.1111/imj.15494
|View full text |Cite
|
Sign up to set email alerts
|

Treatment use and satisfaction in Australian women with endometriosis: a mixed‐methods study

Abstract: Aims: To document the frequency of conventional and complementary treatments used by Australian women with endometriosis and the perceived efficacy of these treatments, and to qualitatively explore women's treatment satisfaction.Background: We do not adequately understand whether Australian women with endometriosis are satisfied with their medical care.Methods: Using a mixed-methods design, 532 women with self-reported endometriosis were recruited from the community. Participants were asked about their medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 38 publications
(66 reference statements)
5
40
0
Order By: Relevance
“…The Irish experiences detailed in our findings add weight to previous literature regarding dissatisfaction with support offered by healthcare professionals (Lukas et al, 2018) and variation in treatments offered (Pettersson and Berterö, 2020). Further, the commonly reported feeling of being 'let down' by healthcare services in Ireland echoed experiences of women in the Australian context (Evans et al, 2021). These findings also support those of Dancet et al (2014) which reported difficulties in accessing care, the need for improved information and education surrounding diagnosis and treatment, and more medical training and expert surgeons.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Irish experiences detailed in our findings add weight to previous literature regarding dissatisfaction with support offered by healthcare professionals (Lukas et al, 2018) and variation in treatments offered (Pettersson and Berterö, 2020). Further, the commonly reported feeling of being 'let down' by healthcare services in Ireland echoed experiences of women in the Australian context (Evans et al, 2021). These findings also support those of Dancet et al (2014) which reported difficulties in accessing care, the need for improved information and education surrounding diagnosis and treatment, and more medical training and expert surgeons.…”
Section: Discussionsupporting
confidence: 72%
“…Rowe et al (2021) further recommends longer-term care planning and a collaborative approach to care incorporating women's selfknowledge and expertise. Evans et al (2021) echoed many of the above points, adding that women with endometriosis felt "Let down" by doctors as a result of experiencing medical gaslighting and needed to fight to be heard (p. 2099). Sbaffi and King (2020) published the only study on endometriosis to date that includes Irish women.…”
Section: Endometriosis Patients' Health Encounter and Health System E...mentioning
confidence: 99%
“…The solo-provider model has been associated with persisting symptoms, long delays in diagnosis, repeated surgeries and low care satisfaction ( Agarwal et al 2021 ). As few as 24% of Australian women with endometriosis are satisfied with the management of their condition, with barriers to accessing interdisciplinary care that addresses functioning beyond infertility and pain one of the main reasons for dissatisfaction ( Evans et al 2021 ).…”
Section: Challenges With the Current Clinical Management Of Endometri...mentioning
confidence: 99%
“…Given the ongoing challenges of pain and symptom management, it is perhaps unsurprising that many people are choosing to engage in self-management ( Armour et al 2019 c , O’Hara et al 2020 ) with as many as 89% of Australian women with endometriosis using complementary and self-care approaches to manage pain ( Evans et al 2021 ). People with endometriosis often need to seek regular care from general practitioners, medical specialists (e.g.…”
Section: Self-management For Endometriosis Symptomsmentioning
confidence: 99%
See 1 more Smart Citation